Mothers' experiences of feeling maternal ambivalence : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, New Zealand - Gilmour, Sarah Jane (Massey University, 2020)
Feelings related to our experiences of motherhood are often complex. One such feeling is maternal ambivalence, the intertwinement of deep love and dislike of motherhood. Yet, the freedom to share these feelings remains subjugated within our patriarchal neoliberal society. Dominant cultural narratives such as the motherhood mandate prime us to naturally enjoy mothering, while we are also required to maintain the demanding care standards of the ‘good mother’. Feelings of maternal ambivalence have frequently been theorised as a negative and harmful psychopathology of motherhood. However, there has been a dearth of research understanding mothers’ feelings of maternal ambivalence within their day-to-day mothering experience. During conversational teller-led interviews, ten mothers shared their experiences of having mixed feelings of motherhood for the current study. Feminist phenomenology epistemology and methodology was employed to enable an understanding of how we traverse feelings of both enjoying and disliking motherhood as socially contextualised, embodied mothers. Analysis tells how feeling maternal ambivalence began at differing stages within motherhood; before or during pregnancy, at birth, or once we had a baby in our arms. It arose within day-to-day mothering experiences such as sleep deprivation, loneliness or boredom. Our experiences of mothering events which moved us outside the gendered cultural motherhood narratives we had been told to expect, also opened up mixed feelings of motherhood. How our bodies were treated within our biomedical health system influenced our feelings towards motherhood. Feelings of maternal ambivalence ebb and flow through our lives changing shape and form as we grow, change and transition through our mothering experience. As we experience our mothering transformations within societies culturally embedded beliefs and norms, we are able to understand how our lived environment is influential to how we make sense of, and live our experiences of feeling maternal ambivalence.
Keywords: 420403 Psychosocial aspects of childbirth and perinatal mental health